Building Bridges with Big Brothers Big Sisters: Service-learning Links Between Professional and Civic Engagement Education at a Predominantly Black Institution - Susan McFarlane-Alvarez; Shandra McDonald (The University of Alabama, 2022)
During spring and fall semesters of 2017, Clayton State University students in corporate communication minor courses collaborated with film production majors to raise awareness for Big Brothers Big Sisters of Metropolitan Atlanta. Through this three-way collaboration, students helped to build tactical communication with the objective of increasing interest among potential volunteers for the organization's mentoring program. The deliverables included three videos that Big Brothers Big Sisters used in its drive to increase the number of volunteer mentors in the communities for both the organization and Clayton State. This paper examines the importance of community-engaged service-learning for a student population at a minority-serving predominantly Black institution in Morrow, Georgia, part of the Atlanta metropolitan area. As part of Clayton State's broader community engagement initiative, this collaboration is being evaluated using a case study design. Consequently, we examine the interdisciplinary roots of the initiative while positioning professional and civic education as simultaneously achievable. Ultimately the research positions Clayton State as a centrifuge for collaborative experience, which serves this dual purpose.